What is the impact of shift work on the psychological functioning and resilience of nurses? An integrative review - Tahghighi, Mozhdeh; Rees, Clare; Brown, Janie; Breen, Lauren; Hegney, Desley (Blackwell Publishing Ltd, 2017)
Aim: To synthesize existing research to determine if nurses who work shifts have poorer psychological functioning and resilience than nurses who do not work shifts. Background: Research exploring the impact of shift work on the psychological functioning and resilience of nurses is limited compared with research investigating the impact of shifts on physical outcomes. Design: Integrative literature review. Data Sources: Relevant databases were searched from January 1995-August 2016 using the combination of keywords: nurse, shift work; rotating roster; night shift; resilient; hardiness; coping; well-being; burnout; mental health; occupational stress; compassion fatigue; compassion satisfaction; stress; anxiety; depression. Review Methods: Two authors independently performed the integrative review processes proposed by Whittemore and Knafl and a quality assessment using the mixed-methods appraisal tool by Pluye et al. Results: A total of 37 articles were included in the review (32 quantitative, 4 qualitative and 1 mixed-methods). Approximately half of the studies directly compared nurse shift workers with non-shift workers. Findings were grouped according to the following main outcomes: (1) general psychological well-being/quality of life; (2) Job satisfaction/burnout; (3) Depression, anxiety and stress; and (4) Resilience/coping. We did not find definitive evidence that shift work is associated with poorer psychological functioning in nurses. Overall, the findings suggest that the impact of shift work on nurse psychological functioning is dependent on several contextual and individual factors. Conclusion: More studies are required which directly compare the psychological outcomes and resilience of nurse shift workers with non-shift workers.